Evaluasi Perencanaan Geometrik Jalan Berbasis BIM (Studi Kasus: Jalan Banda Aceh Outer Ring Road) - Faisal, Ruhdi; Rifqi, Arif; Salmannur, Alfi (Jurusan Teknik Sipil, Fakultas Teknik, Universitas Syiah Kuala, 2024)
An optimal road geometric design considers the efficiency of the time required in the design and construction process. This study aims to determine the difference in the results of road geometric calculations using AutoCAD Civil 3D with manual calculations in the case study of Banda Aceh Outer Ring Road (BORR) STA 0+000 - STA13+364.40. The method used for road geometric calculations refers to the 2011 AASHTO standard. However, in terms of planning criteria, it follows the 2021 Road Geometric Design Guidelines standard. The horizontal alignment design produces 9 bends, namely 2 FC curves and 7 SCS curves. In the vertical alignment planning, there are 4 convex vertical curves and 6 concave vertical curves with slopes between 0.00% and 5.80%, which are below the maximum slope of 6%. The length of Lv in the design of concave and convex vertical arches meets the criteria determined by the value of K. Based on the results obtained, the use of AutoCAD Civil 3D has proven effective in assisting the calculation and design of design drawings simultaneously so that the work process becomes more efficient, concise, and minimizes human error.